Xenografting as a Tool to Preserve Endangered Species: Outcomes and Challenges in Model Systems - Paula C. Mota; João Ramalho-Santos; Stefan Schlatt (Veterinary Medicine International)
The use of testis tissue xenografting as a valuable tool to rescue endangered and genetically valuable individuals that die young or otherwise fail to produce sperm has been the subject of much interest. Although the technique has been successfully applied to a wide variety of species, little is known about what determines the outcome. Furthermore, to improve the applicability of xenografting, new methods to preserve and transport testis tissue from valuable animals are emerging. However, one major issue remains: the application of xenografting implies the development of subsequent ART techniques to produce offspring from the recovered material. This paper focuses on these three aspects of testis tissue xenografting as a tool for rescuing endangered and valuable genetic pools.